G9a Correlates with VLA-4 Integrin and Influences the Migration of Childhood Acute Lymphoblastic Leukemia Cells - Madrazo, Elena (Cancers (Basel), 2018)
Acute lymphoblastic leukemia (ALL) is the most common pediatric cancer. As ALL progresses, leukemic cells cross the endothelial barrier and infiltrate other tissues. Epigenetic enzymes represent novel therapeutic targets in hematological malignancies, and might contribute to cells’ capacity to migrate across physical barriers. Although many molecules drive this process, the role of the nucleus and its components remain unclear. We report here, for the first time, that the expression of G9a (a histone methyltransferase related with gene silencing) correlates with the expression of the integrin subunit α4 in children with ALL. We have demonstrated that G9a depletion or its inhibition with BIX01294 abrogated the ability of ALL cells to migrate through an endothelial monolayer. Moreover, G9a-depleted and BIX01294-treated cells presented bigger nuclei and more adherent phenotype than control cells on endothelial monolayers. Blocking G9a did not affect the cell cytoskeleton or integrin expression of ALL cell lines, and only its depletion reduced slightly F-actin polymerization. Similarly to the transendothelial migration, G9a inhibition impaired the cell migration induced by the integrin VLA-4 (α4β1) of primary cells and ALL cell lines through narrow spaces in vitro. Our results suggest a cellular connection between G9a and VLA-4, which underlies novel functions of G9a during ALL cell migration.